PARADIGMA FILOSOFIS LEGAL REASONING ANTARA LEGAL POSITIVISM DAN HISTORICAL JURISPRUDENCE SUATU ANALISIS - Barus, Zulfadli (E-Journal Widya Yustisia, 2005)
Legal research is done if an issue arises that reflects contradiction between the ideal law and real law. Factors influencing gaps in the law related to a certain issue can be determined by legal reasoning. There are two types of legal research namely 1) normative and 2) sociological research. Normative research is based on rationalism, positivism, coherence, a priori, analysis deduction,systematic, literature study, secondary data and qualitative analysis. Sociological research is based on empirical, historica, correspondence, a posteriori, synthesis, induction, systematic, field study, primary data and quantitave analysis. Legal normative research is influenced by systemic reasoning while sociological research is influenced by critical reasoning.